2015
DOI: 10.1177/0741088315614566
|View full text |Cite
|
Sign up to set email alerts
|

How Magnets Attract and Repel

Abstract: K6015, a South Korean firm seeking to commercialize its magnet technology in the US market, entered a technology commercialization training program structured as a competition. Through this program, K6015 (and others in the program) used several genres to progressively interest different sets of stakeholders. To understand how K6015 applied these genres, we analyze this case study in terms of interessement, a concept from actornetwork theory, and standing sets of transformations, a related concept from workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Mapping these exchanges using AT (see Figures 4 and 6) facilitates detailed analysis of how the digital tool might be defining and shaping the encounter. ANT's interest in power and persuasion, in the interessement and enrolment in net-work (see Callon, 1986;Spinuzzi, 2008;and Spinuzzi et al, 2016), is difficult to trace using AT. The analysis ANT facilitates specifically helps us see how larger historical dynamics intertwine with the mundane material affordances of the tool, impinging on the activity's division of labor and creating the conditions of "silence" into which a process of "inventing" another becomes visible as a dynamic in the writing activity.…”
Section: Example Whatsapp Encounter: Esteban/johnmentioning
confidence: 99%
“…Mapping these exchanges using AT (see Figures 4 and 6) facilitates detailed analysis of how the digital tool might be defining and shaping the encounter. ANT's interest in power and persuasion, in the interessement and enrolment in net-work (see Callon, 1986;Spinuzzi, 2008;and Spinuzzi et al, 2016), is difficult to trace using AT. The analysis ANT facilitates specifically helps us see how larger historical dynamics intertwine with the mundane material affordances of the tool, impinging on the activity's division of labor and creating the conditions of "silence" into which a process of "inventing" another becomes visible as a dynamic in the writing activity.…”
Section: Example Whatsapp Encounter: Esteban/johnmentioning
confidence: 99%
“…Also, the review showed that some empirical research (see next section) were based on data collected from TV shows. Daly and Davy (2016a;2016b), for example, analyzed pitches from the Dragon's Den while Moreau (2018) explored pitches from its American counterpart, Shark Tank.…”
Section: Identifying Focuses Definitions and Purposes Of Pitchmentioning
confidence: 99%
“…For eliciting data, these studies use ethnographic, anthropological and cultural techniques, such as the analysis of decks, in-depth interviews with pitchers, investors and mentors, use of field notes, audio recording and videotaping. Spinuzzi (2014Spinuzzi ( , 2015aSpinuzzi ( , 2015bSpinuzzi ( , 2016aSpinuzzi ( , 2016bSpinuzzi ( , 2018 analyzed the transformations of a pitch as contestants receive feedback in competitions or evaluation settings. To identify changes, Spinuzzi et al (2014Spinuzzi et al ( , 2015aSpinuzzi et al ( , 2015b focused on the pitch deck, a set of slides that are usually used along the oral presentation.…”
Section: Linguistic and Discursive Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is evidence of the criteria used by investors to evaluate an innovation project, there is scarce linguistic and discursive description of the genres of innovation according to these kinds of variables (See Moya & Molina, 2017;Spinuzzi, Nelson, Thomson, Lorenzini, French, Pogue, Durback & Momberger, J. 2014;Spinuzzi, Nelson, Thomson, Lorenzini, French, Pogue, Burback & Momberger, 2015a;Spinuzzi, Thomson, Burback, Pogue, Lorenzini, Nelson, French & Momberger, 2015b;Spinuzzi, Jakobs & Pogue, 2016a;Spinuzzi, Nelson, Thomson, Lorenzini, French, Pogue & London, 2016b).…”
Section: The DI and The Extra-linguisticmentioning
confidence: 99%